A new biosurfactant-producing strain, Fictibacillus nanhaiensis ME46, isolated from an oil field in China - Li, Jia-Yi (Environmental technology, 2024)
The genus Fictibacillus contains twelve species significant in the synthesis of cellulose-degrading enzymes and phenylalanine dehydrogenase, isolated mainly from marine sedimentary environments. Here, we report a new biosurfactant-producing strain, Fictibacillus nanhaiensis ME46, isolated from Daqing oil field in China. The biosurfactant extracted from Strain ME46 was determined as surfactin, one of the representative families of lipopeptide biosurfactants. The yield of the surfactin produced by strain ME46 was 0.62 g·L-1 as determined by high-performance liquid chromatography, and the critical micelle concentration (CMC) of the surfactin was estimated to be about 68 mg·L-1 and the surface tension at CMC was 35.1 mN·m-1. This study extended our knowledge about the role of the species Fictibacillus nanhaiensis in the ecosystem of natural environments such as the oil field